Integrated Inventory Model for Single Vendor Single Buyer Considering the Level of Product Defects - Arwin Firman Rahmanto; Said Salim Dahda (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
The supply chain is one of the factors that are very influential in the production process in a company. In actual conditions, often in the production process, there are still many defective products that will be sent to buyers. Therefore, this study aims to propose a single-vendor single-buyer inventory model with consideration of the presence of defective products to minimize the total joint inventory cost. An iterative algorithm is used to obtain optimal values of the frequency of shipments and the cycle length resulting in a minimum total joint inventory cost. The results of the numerical examples and sensitivity analysis indicate that proposed integrated model gives a significant cost saving along with a high percentage of defective products. Supply chain atau rantai pasok merupakan salah satu faktor yang sangat berpengaruh dalam proses produksi di suatu perusahaan. Pada kondisi yang sebenarnya, seringkali pada proses produksi masih banyak ditemukan produk cacat yang nantinya akan terkirim kepada pembeli. Oleh karena itu, penelitian ini bertujuan untuk mengusulkan sebuah model persediaan produsen tunggal pembeli tunggal dengan pertimbangan adanya produk cacat guna meminimalkan total biaya persediaan gabungan. Algoritma iteratif digunakan untuk mendapatkan nilai optimal dari frekuensi pengiriman dan lama siklus dalam menghasilkan total biaya persediaan gabungan yang minimum. Hasil dari contoh numerik dan analisis sensivitas menunjukkan bahwa model terintegrasi yang diusulkan memberikan penghematan biaya yang cukup signifikan seiring dengan tingginya persentase produk cacat.